Consumer Intention and Usage Behavior of Live-Streaming Shopping: An Extension of the Unified Theory of Acceptance and Use of Technology - Sun, Xuemei (The Journal of Behavioral Science, 2022)
Live-streaming shopping is increasing in both popularity and profitability throughout the world. However, there are limited studies that have focused on the psychological motivation of customers regarding information technology for live-streaming shopping behavior. Grounded in the unified theory of acceptance and use of technology-2 model, this study was the first to include trust, perceived risk, deal proneness, and consumer innovativeness simultaneously to examine consumer intention and usage behavior of live-streaming shopping. Additionally, the moderating effects of demographic characteristics involving gender, age, and experience were included. A convenience sampling method was used to gather data from 860 Chinese live-streaming users in mainland China. The Cronbach’s alpha coefficient showed overall scale reliability was .97. The results of PLS-SEM analysis confirm that the present model has a medium capacity to explain behavioral intention (R2 = .47) and usage behavior (R2 = .50). Besides, “habit” has been found as the strongest predictor of both behavior intention (β = .28, p < .001) and actual use (β = .32, p < .001) of live-streaming shopping. The finding suggests the importance to encourage consumers to use live-streaming shopping. Interestingly, the results provide valuable insights that can be applied by vendors to enhance intention to use live-streaming shopping among consumers by improving and retaining their hedonic motivation and trust.